Geriatric cardiology: We are not forgetting the elderly - Nuñez Delgado, Rocio del Pilar (2024)
Geriatric Cardiology was born as a need for the comprehensive, individualized, holistic, strategic evaluation of the elderly, in itself heterogeneous; in conjunction with their geriatric syndromes such as frailty, cognitive impairment, sarcopenia, physical dysfunction, falls; in addition to its multimorbidity, its polypharmacy; with respect to cardiovascular diseases such as heart failure, atrial fibrillation, coronary disease, valvular disorders; ethereal population, which in many clinical trials have been excluded, and do not have a representativeness in the development of the current clinical guidelines for the correct diagnosis, evaluation and treatment of said cardiovascular diseases; Geriatric cardiology is therefore collaborative, it is multidisciplinary, it prioritizes quality of life more than longevity in the patient, based on geriatric principles with the implementation of scales to assess frailty, cognition, malnutrition, depression; that will help decision-making about the performance of cardiovascular procedures to operations or pharmacological treatments; that could worsen the morbidity and mortality of an older adult; help the process of deprescription, palliative care or care at the end of life.